(untitled) - Brenda Hale (London,Dayton, Ohio, 2002)
This book provides a wealth of material drawn not only from familiar primary sources but from studies in related disciplines. This new edition has been fully revised to include all significant statute and case law developments since the fourth edition, including the implications of the Family Law Act 1996 and the Human Rights Act 1998. It also incorporates the increasing recognition in the law of the significance of domestic violence, and the long-awaited Adoption and Children Bill
Keywords: Domestic relations; Domestic relations; Family policy